STUDY OF DIKE EFFECTS TO CONTROL SEDIMENTATION PROCESS ON PATIMBAN’S PORT PLAN USING COMPUTATION MODELING - Mardi Wibowo; Widjo Kongko (Majalah Ilmiah Pengkajian Industri; Journal of Industrial Research and Innovation, 2023)
The development of the international port of Patimban in Subang is very urgent. The port is expected to support the Tanjung Priok port in Jakarta which is unable to meet the loading and unloading needs of business operators, especially in West Java. In port development planning one of the main problems of physical chemical aspects is sedimentation and erosion process. The purpose of this modeling is to know the sedimentation and erosion pattern around the location plan of port development. The result of modeling is expected to be the initial consideration in designing the Patimban Port. Modeling of sediment transport is done by using MIKE21 Sand Transport module software by entering geophysical data of field survey result such as bathymetry, sea level, river flow and characteristic of existing sediment. Modeling is done both in west season and east season for 1 year (October 2016-September 2017). Based on the result of point extraction on the modeling result, it is known that the influence of dike significantly reduces the bed level change in the harbor channel about 46.45 - 82.28% (for dike 2 m) and about 55.01 - 88.94% (for dike 4 m). While, based on the result of the area extraction, it is known that the influence of the dike on the bed level change in the harbor channel is significant, that is to decrease the average of bed level change by 77.58% (for dike 2m) and 81.02% (for dike 4m).